PENGARUH LIKUIDITAS, LEVERAGE, DAN PROFITABILITAS TERHADAP FINANCIAL DISTRESS (STUDI EMPIRIS PADA PERUSAHAAN SUB SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2019) - Pujiati, Herni; Melati, Dinda (Institut Teknologi dan Bisnis Swadharma, 2020)
This study aims to analyze the influence of Liquidity, Leverage, and Profitability on Financial Distress in Transportation Sub-Sector Companies listed on the Indonesia Stock Exchange 2017 - 2019. The research methodology used is a quantitative method with combined data from time series panels and cross-sectional secondary data, using secondary data obtained from the Indonesia Stock Exchange website and the company's website. The sampling technique used purposive sampling with data from 2017 - 2019. The data analysis technique used is binary logistic regression by conducting descriptive statistical tests, classical assumption tests (multicollinearity), hypothesis tests using partial significant test, likelihood ratio, and R2 test (coefficient of compound determination). The results of this study indicate that partially the liquidity variable has a positive effect and is not significant on financial distress, the leverage variable has a positive effect and significant on financial distress, and profitability has a negative effect and is significant on financial distress. Meanwhile, simultaneously the independent variables liquidity, leverage, and profitability together have a significant relationship to the dependent variable, namely financial distress. The coefficient of determination of this study shows a figure of 50,31%. This shows that the variation of the independent variables of liquidity, Leverage, and Profitability can explain the variations in the ups and downs of the Financial Distress variable by 50,31% while the remaining 49,69% is influenced by other independent variables